2020
DOI: 10.1016/j.ecolmodel.2020.109088
|View full text |Cite
|
Sign up to set email alerts
|

Can DEB models infer metabolic differences between intertidal and subtidal morphotypes of the Antarctic limpet Nacella concinna (Strebel, 1908)?

Abstract: Studying the influence of changing environmental conditions on Antarctic marine benthic invertebrates is strongly constrained by limited access to the region, which poses difficulties to performing long-term experimental studies. Ecological modelling has been increasingly used as a potential alternative to assess the impact of such changes on species distribution or physiological performance. Among ecological models, the Dynamic Energy Budget (DEB) approach represents each individual through four energetic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 118 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Marn and colleagues (2019) found that DEB parameters differed between Mediterranean and North Atlantic loggerhead turtles, and that life-history differences between these populations could not be explained as a direct result of environmental differences between their respective habitats. In contrast, Guillaumot and colleagues (2020) were unable to determine differences in DEB parameters between intertidal and subtidal ecotypes of the Antarctic limpet, despite clear morphological divergence. As such, there is little consensus on the extent to which DEB parameters can vary within a single species.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Marn and colleagues (2019) found that DEB parameters differed between Mediterranean and North Atlantic loggerhead turtles, and that life-history differences between these populations could not be explained as a direct result of environmental differences between their respective habitats. In contrast, Guillaumot and colleagues (2020) were unable to determine differences in DEB parameters between intertidal and subtidal ecotypes of the Antarctic limpet, despite clear morphological divergence. As such, there is little consensus on the extent to which DEB parameters can vary within a single species.…”
Section: Introductionmentioning
confidence: 85%
“…This assumption is central to analyses of interspecific patterns of variation in DEB parameters, yet little is known about how much these parameters actually vary within species. To our knowledge, only two studies have employed DEB theory to quantify life-history differences between natural populations of the same species (Marn et al, 2019; Guillaumot et al, 2020). Marn and colleagues (2019) found that DEB parameters differed between Mediterranean and North Atlantic loggerhead turtles, and that life-history differences between these populations could not be explained as a direct result of environmental differences between their respective habitats.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Guillaumot et al. (2020) were unable to determine differences in DEB parameters between intertidal and subtidal ecotypes of the Antarctic limpet Nacella concinna , despite clear morphological divergence. There is little consensus on the extent to which DEB parameters vary within species, or on the causes of failure to detect differences in DEB parameters between ecologically and morphologically distinct populations.…”
Section: Introductionmentioning
confidence: 92%
“…It has been successfully applied to a broad range of organisms such as Icelandic capelins (Einarsson et al 2011), the Pacific oyster (Ren and Ross 2001) and even endoparasitic wasps (Llandres et al 2015). Recent studies (Guillaumot et al 2020;Groeneveld et al 2020) emphasize how individual based modelling and DEB-theory can be especially useful for studying Antarctic species when habitat access is limited and data is sparse. The framework of bioenergetic modelling further holds the potential to project from individuals to population dynamics, which makes the development of a DEB-based krill model particularly interesting (Martin et al 2013).…”
Section: Introductionmentioning
confidence: 99%